Managing Pandemic Responses with Health Informatics – Challenges for Assessing Digital Health Technologies - Magrabi, Farah; Ammenwerth, Elske; Craven, Catherine K.; Cresswell, Kathrin; De Keizer, Nicolet F.; Medlock, Stephanie K.; Scott, Philip J.; Wong, Zoie Shui-Yee; Georgiou, Andrew (Yearbook of Medical Informatics, 2021)
Objectives: To highlight the role of technology assessment in the management of the COVID-19 pandemic.Method: An overview of existing research and evaluation approaches along with expert perspectives drawn from the International Medical Informatics Association (IMIA) Working Group on Technology Assessment and Quality Development in Health Informatics and the European Federation for Medical Informatics (EFMI) Working Group for Assessment of Health Information Systems.Results: Evaluation of digital health technologies for COVID-19 should be based on their technical maturity as well as the scale of implementation. For mature technologies like telehealth whose efficacy has been previously demonstrated, pragmatic, rapid evaluation using the complex systems paradigm which accounts for multiple sociotechnical factors, might be more suitable to examine their effectiveness and emerging safety concerns in new settings. New technologies, particularly those intended for use on a large scale such as digital contract tracing, will require assessment of their usability as well as performance prior to deployment, after which evaluation should shift to using a complex systems paradigm to examine the value of information provided. The success of a digital health technology is dependent on the value of information it provides relative to the sociotechnical context of the setting where it is implemented.Conclusion: Commitment to evaluation using the evidence-based medicine and complex systems paradigms will be critical to ensuring safe and effective use of digital health technologies for COVID-19 and future pandemics. There is an inherent tension between evaluation and the imperative to urgently deploy solutions that needs to be negotiated.
Keywords: Health information technology; COVID-19; evaluation studies; program evaluation